Investigation of RMP induced density pump-out on EAST. (3rd October 2018) - Wang, S.X.; Liu, H.Q.; Jie, Y.X.; Ding, W.X.; Zeng, L.; Sun, Y.W.; Lian, H.; Zhu, X.; Zou, Z.Y.; Lyu, B.; Li, Y.Y.; Zang, Q.; et al.
Abstract: Density pump-out has been observed on the experimental advanced superconducting tokamak under the conditions of mitigated or totally suppressed edge localized modes with n = 2 external resonant magnetic perturbation (RMP), associated with decreased core density and degradation of particle confinement. In order to investigate the particle transport during RMP induced density pump-out, density modulation using supersonic molecular beam injection is performed to obtain the particle transport coefficients. The results show that the diffusive coefficient becomes larger and the inward convection velocity decreases towards the plasma edge after RMP. The measured radial electric field ( E r ) became less negative in the plasma edge near rho 0.97 and consequently, the E × B shearing rate was reduced significantly, which is consistent with increased density fluctuations.